Prävalenz, Risikogruppen und Motive der Solariennutzung in Deutschland - Schneider, S.; Breitbart, E. W.; Greinert, R.; Diehl, Katharina; Goerig, Tatiana (Hautarzt, 2016)
Background: Ultraviolet (UV) radiation of sunbeds has been classified carcinogenic by the International Agency for Research on Cancer (IARC). Unlike in other countries the available data on the important risk factor has been lacking until recently in Germany. Objectives: The SUN-Study 2012 (Sunbed-Use: Needs for Action Study) aimed at identifying epidemiological prevalence data concerning this completely preventable risk factor. Materials and methods: A total of 4,851 participants aged 14–45 years were selected from the German population in a representative manner and were surveyed via standardized telephone interviews. The survey period was split into a summer and a winter wave in order to take possible season effects into account. Results: Four out of 10 Germans aged 14–45 years (39.2 %; 95 % CI 37.8–40.6 %) have ever used a sunbed. Within the last year 14.6 % (95 % CI 13.6–15.6 %) visited a sunbed. Current users reported six visits per year on average and every twentieth reported a family history of cutaneous malignant melanoma in first-degree relatives. More than 5 % of minors currently used sunbeds despite the nationwide ban, mostly at unsupervised locations. Half of those minors did not know about the legal ban of sunbed use for minors. Conclusions: Our study proves that sunbed use which is an important risk factor for skin cancer is widely used. Moreover, considerable information deficits about health risks exist among the German population.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Melanoma; Risk factors; Skin cancer; Suntanning; Ultraviolet light